PENGGUNAAN MODEL PROJECT BASED LEARNING DENGAN METODE PEER TUTORING DALAM PEMBELAJARAN HUKUM ARCHIMEDES - Uada, Putri Angel; Poluakan, Cosmas; Rampengan, Alfrie M.; Taunaumang, Heindrich; Mandang , Theresje; Tumalun, Nicky K. (Charm Sains: Jurnal Pendidikan Fisika, 2025)
This article aims to determine the effect of using the project-based learning model with the peer tutoring method in teaching Archimedes' principle in physics. This research was conducted at SMA Negeri 1 Tombatu using a quantitative research design with a one-group pre-test post-test design. The use of the project-based learning model with the peer tutoring method enabled students to understand the material taught, based on student learning outcomes, namely the pre-test results showed that the average score of students was 35.83 and increased to 84 in the post-test results. Thus, it can be concluded that the use of the project-based learning model with the peer tutoring method has a significant effect on student learning outcomes in physics learning on Archimedes' principle.